DEVELOPMENT OF AGROTOURISM BASED ON LOCAL WISDOM IN BALI COUNTRYSIDE SIDEMEN AS AN EFFORT TOWARD SUSTAINABLE TOURISM - Anang Ma’rup; Ni Wayan Purnami Rusadi (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
The Bali Countryside Sidemen area holds great potential to be developed as an agrotourism destination that combines the charm of rural landscapes, traditional farming practices, and the local wisdom of the community. Located in Sukahet Village, Sidemen District, Karangasem Regency, this area has the opportunity to become a model of sustainable agricultural tourism that supports food security, environmental education, and economic empowerment of local residents. However, the development of this destination still faces several challenges, such as limited promotion, inadequate tourism infrastructure, underdeveloped attractions, and poor accessibility. This study aims to formulate a development strategy for community-based agrotourism. A qualitative approach was used, involving interviews with five key informants consisting of tourism actors and local farmers, supported by documentation and direct field observation. The analysis was based on four key tourism elements (4A): attraction, accessibility, amenities, and ancillary services, with a focus on the agricultural context. The results show that strengthening promotion, creating educational attractions such as planting and harvesting activities, processing local agricultural products, and providing environmentally friendly accommodations rooted in farming culture are strategic steps to unlock the area’s potential. The main recommendation of this study is the collaboration between farmers, tourism entrepreneurs, and village government to establish an inclusive and sustainable agrotourism system.